DETERMINANTS OF CONTINUOUS USAGE BEHAVIOR OF SOCIAL COMMERCE : A STUDY OF SMALL ONLINE VENDORS IN PAKISTAN - Muhammad Zaigham, Raza; Mahani Mohammad, Abdu Shakur; Shahnawaz, Saqib (SOUTH FLORIDA PUBLICATIONS, 2025)
Objective: The objective of this study is to investigate determinants of continuous usage behavior of small online vendors in social commerce under government support as moderator. Theoretical Framework: Social Exchange Theory and TOE framework provide theoretical underpinnings of this study to understand the continuous usage behavior in social commerce. Method: In this regard, data was collected from the small online vendors under convenience sampling. In this case, a survey approach was employed, and 500 questionnaires were distributed among the participants, out of which 392 were returned. Partially filled and incomplete responses were discarded and 376 useful responses were used for data analysis purpose. Results and Discussion: Structural equation modeling has been used for data analyses through Smart PLS 4.0 software. All of the validity and reliability indicators for the measurement and structural models were found statistically fit. Research Implications: According to path estimation, perceived usefulness, financial resources, and Security concerns have all been found statistically significant. In the case of moderation, the govt support has been proven a factor in mitigating the security concerns for continuous usage behavior of social commerce. Originality/Value: This study investigated the unexplored determinants related to continuous usage behavior in the context of social time as a moderator in the study. It has not been tested before in this context of small online vendors, that how government support moderates the small online vendors in conjunction with the TOE framework to social commerce continuous usage behavior.